2012
DOI: 10.1002/pd.3964
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery Doppler velocimetry and obstetric outcomes in connective tissue diseases diagnosed during the first trimester of pregnancy

Abstract: Women with undiagnosed CTDs have higher rates of bilateral UtA Doppler notches throughout pregnancy and increased rates of adverse pregnancy outcomes than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…High UtA-PI values have been associated with adverse pregnancy outcomes. An abnormal uterine artery Doppler pattern has been defined as a mean UtA-PI higher than the 95th percentile value, and this cut-off may be useful in clinical practice for PE screening among high-risk populations 22,25,[29][30][31] . In our study, the 95th percentile value for mean UtA-PI was 2.3 (range: 1.9-2.5).…”
Section: Discussionmentioning
confidence: 99%
“…High UtA-PI values have been associated with adverse pregnancy outcomes. An abnormal uterine artery Doppler pattern has been defined as a mean UtA-PI higher than the 95th percentile value, and this cut-off may be useful in clinical practice for PE screening among high-risk populations 22,25,[29][30][31] . In our study, the 95th percentile value for mean UtA-PI was 2.3 (range: 1.9-2.5).…”
Section: Discussionmentioning
confidence: 99%
“…Markers of endothelial cell activation or damage and carotid intima‐media thickness are increased among subjects with UCTD, whereas brachial artery flow‐mediated vasodilatation is reduced, suggesting systemic endothelial dysfunction associated with autoimmune serological abnormalities . The increased resistance of blood flow velocities of uterine arteries in the first and second trimesters of pregnancy, as measured by Doppler ultrasound, suggests that surrogate markers of adequate early placentation are impaired among pregnant subjects with UCTD compared to controls …”
Section: Biological Basis Of Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Extravillous trophoblast invasiveness could also be impaired by immune‐mediated mechanisms involving the local production of cytokines . Whatever the mechanism involved, compared to controls, pregnancies in women with rheumatic diseases are characterized by higher rates of defective placentation and increased resistance in maternal‐fetal circulation, as demonstrated by Doppler ultrasound studies . Undifferentiated connective tissue diseases (UCTDs) are a heterogeneous group of systemic autoimmune rheumatic disorders characterized by clinical and serological findings that do not fulfill a definite diagnosis of rheumatic disease .…”
Section: Introductionmentioning
confidence: 99%
“…Antinuclear antibodies and inflammation in UCTD may impair platelet activity, unbalance coagulation/anticoagulation, increase the risk of thrombosis, cause collagen synthesis defect and endothelial dysfunction [8][9][10]. Therefore, it could increase uterine artery resistance, inhibit placenta development and remodelling, and thus increase the risk of pre-eclampsia, intrauterine growth retardation (IUGR), small for gestational age infant (SGA) and recurrent spontaneous abortion (RSA) [4,[11][12][13][14]. Spinillo found that women with UCTD had a higher rate (39.0%) of at least 1 spontaneous pregnancy loss than healthy controls with an odds ratio of 5.92 (95% CI, 2.1-17.8) [14].…”
Section: Introductionmentioning
confidence: 99%